Fatigue strength of corroded bolted connection (Fracture and Structural Integrity, 2017)
This note summarizes some recent investigation results on the behavior of corroded steel bolted joints under uniaxial fatigue loading. Fatigue test specimens, were made up using S355 structural steel plates joined together with preloaded M12 bolts of class 10.9 with a geometry that corresponds to the Δσ = 112 MPa EC3 detail category. The accelerated corrosion process was accomplished using an electrolyte consisting of an aqueous 5% NaCl solution whereby the specimens were treated. In particular, during the corrosion process specimens were repeatedly immersed for 2 minutes in the electrolyte and then removed keeping them 60 minutes long in free air at 35 °C. An atmospheric corrosion in marine-industrial environment is wellrepresented through corrosion test. Fatigue loading tests and surface morphology measurement of uncorroded and corroded specimens were performed and the results were compared.
Keywords: Fatigue strength; Corrosion; Bolted connections; Steel bridge